Transformasi Kepemimpinan Digital dan Teknologi 5.0 Di Era AI Dalam Organisasi Pendidikan - Rois Mahmudi; Siti Aimah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to analyze effective digital leadership strategies in educational organizations in the era of AI and digital technology 5.0, and to explore how educational leaders can utilize these technologies to improve the quality of management, decision-making, and innovation in the learning process. This study uses a qualitative approach with a case study type conducted at SMA Darussalam Blokagung Banyuwangi, the largest private school in Banyuwangi whose leaders strongly support the use of AI to improve learning outcomes. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. Data were analyzed using the Miles and Huberman interactive data analysis model consisting of three main stages: data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that digital leadership in this Islamic school has succeeded in upgrading teacher resources in technological skills, AI utilization, decision-making, and change management strategies to realize the school's vision. The success of this transformation is influenced by the readiness of organizational resources, digital policies, and a culture of innovation that has been built since 3 years ago. This research contributes to providing insight into the role of digital leadership in improving the effectiveness of educational management in the era of advanced technology, so these findings are expected to be the basis for developing an adaptive and sustainable digital leadership model for private schools in the regions. Keywords: Digital leadership, AI, Technology 5.0, Educational Organization